2021
DOI: 10.3389/fvets.2021.629121
|View full text |Cite
|
Sign up to set email alerts
|

The Initial Months of COVID-19: Dog Owners' Veterinary-Related Concerns

Abstract: Veterinarians, like many other professions, were significantly impacted by the onset of COVID-19 in the spring of 2020. Standard practices were disrupted, and veterinary hospitals had to quickly modify standard protocols to safely serve their clients and patients. The purpose of this study was to better understand dog owners' fears and concerns pertaining to veterinary care and obtainment of pet care products and food during the lock down phase of a pandemic to be better prepared to address these concerns now … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 3 publications
6
34
0
Order By: Relevance
“…Both quantitative and qualitative data indicated that relatively few participants had experienced issues ensuring the welfare of their companion animals during the pandemic. Despite this finding, qualitative data suggested that proper care of companion animals was a significant source of worry for guardians during this time; this finding is corroborated by other research conducted during the pandemic [ 72 , 73 ]. Previous research has also indicated that people are willing to delay hospitalisation [ 74 ] or refuse access to support services [ 75 ] for the sake of their companion animals, and similar attitudes were present in the current study.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Both quantitative and qualitative data indicated that relatively few participants had experienced issues ensuring the welfare of their companion animals during the pandemic. Despite this finding, qualitative data suggested that proper care of companion animals was a significant source of worry for guardians during this time; this finding is corroborated by other research conducted during the pandemic [ 72 , 73 ]. Previous research has also indicated that people are willing to delay hospitalisation [ 74 ] or refuse access to support services [ 75 ] for the sake of their companion animals, and similar attitudes were present in the current study.…”
Section: Discussionsupporting
confidence: 74%
“…Participants were often more concerned about the potential negative impact of COVID-19 on their companion animals than on themselves. For instance, while most participants had no concerns about transmitting SARS-CoV-2 either to or from their companion animals, a slightly larger proportion reported being concerned about transmitting the virus to their companion animals than the reverse; this finding is replicated in other research [ 73 ]. Therefore, the relationship between companion animal guardianship and well-being during the pandemic may have been confounded by the unique stresses associated with keeping companion animals.…”
Section: Discussionsupporting
confidence: 60%
“…This paper focuses on the survey questions pertaining to the impact of dogs and cats on guardians' COVID-related feelings. Other aspects of the study (e.g., changes in time spent with companion animals and the impact of these changes; concerns related to caring for a companion animal, veterinary care, and the ability to obtain and afford pet supplies) have been reported previously [50,51]. Participants included an international sample of cat and dog guardians over the age of 18.…”
Section: Methodsmentioning
confidence: 99%
“…Fears intensified as the number of cases grew exponentially and scientific knowledge of the means of transmission was limited and contradictory [2]. To mitigate the potential spread of COVID-19, numerous governmental agencies issued public health mandates requiring Research conducted during the initial months of COVID-19 has shown that while many companion animal guardians were worried about being able to provide for their companion animal and access veterinary medical services [48][49][50][51][52][53][54], they were grateful for the increased quality time with them and reflected on how their companion animal offered a decreased sense of loneliness [49,54,55]. Given the strong connections people have with their companion animals, and the potential benefits of companion dogs and cats, this study hypothesized that companion dogs and cats would positively impact guardians' mental health.…”
Section: Introductionmentioning
confidence: 99%
“…As noted by Wiltzius et al suggesting that people with limited means should not have pets is an "untenable solution" (21). Additionally, with research suggesting that pets play a critical role in mitigating COVID-19 related stress (29)(30)(31), and numerous antidotal reports that pet adoptions have dramatically increased since the pandemic began, it is more critical than ever to support these vulnerable pet owners. Assisting these families that struggle with financial constraints that prevent them from accessing veterinary care could help them keep their pets at home (20).…”
Section: Discussionmentioning
confidence: 99%